Dietary options of people with specific dietary requirements in the National Park Bohemian Switzerland - Kudrová, Aneta; Bejdáková, Blanka; Dvořák, Antonín; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2022)
This thesis deals with the dietary options of people with specific dietary requirements during hiking, specifically the dietary options of people with coeliac disease, vegetarians, vegans, and people eating without milk, on the hiking route in the National Park Bohemian Switzerland. The thesis also examines the experience of people with specific dietary requirements with food establishments along hiking routes. The result of the research is a gap on the market between the demand of people with dietary requirements for meals and the supply of meals by food establishments along hiking routes.
Vedoucí práce: Blanka Bejdáková
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: cestovní ruch [obor bakal. práce]; bakalářské práce; bachelor's theses